The Importance of Improving the Performance of Kampung Performance on Community Services at Kalisusu Office, Nabire District - Petrus Mangambe (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In Development Planning in Dagouto Village, Paniai Timur District, Paniai Regency "The purpose of this study was to determine and find the relationship between variables, namely the Role of the Village Head (independent variable) and Village Development Planning (dependent variable), using descriptive methods. The research subjects were 50 people, namely village officials and community leaders from Dagouto Village. (1) The role of the Village Head with indicators of Motivation, Coordination, and Supervision has not gone well. Leadership, the village head has not been in accordance with what was expected by the Dagouto village community. (2) Village Development Planning with indicators, Meetings/Meetings, Timing and Targeting is also not as expected. These three indicators have not shown a good level of welfare for the people of Dagouto village. The low level of meetings, the low level of punctuality and low targeting shows that the level of the role of the Dagouto village head is still very low.